Eksploitasi Alam dalam Perspektif Sastra: Kajian Ekologi Sastra Novel Tiang Garam Karya Royyan Julian dan Implikasinya pada Pendidikan Literasi Lingkungan - Syaiful Rahman; Dinda Triana Cindi (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
Environmental issues continue to be a global concern, driven by exploitative human behavior that disrupts ecological balance. Literature, as a reflection of reality, often addresses environmental problems through narratives that raise ecological awareness among readers. This study aims to describe the representation of environmental issues in the novel Tiang Garam by Royyan Julian and its relevance to teaching Indonesian Language and Literature. A qualitative descriptive method with an ecocriticism approach was employed. The research data consist of textual excerpts depicting environmental problems, with the primary source being the novel Tiang Garam. Data collection was conducted using observation and note-taking techniques, and data analysis followed the Miles and Huberman model, modified to suit the research needs. The findings highlight three major environmental issues in the novel: (1) deforestation, (2) environmental pollution, and (3) animal exploitation, all resulting from human activities. The conclusion reveals that Tiang Garam is highly relevant as teaching material for Indonesian Language and Literature, particularly in fostering students' ecological awareness and encouraging responsible attitudes toward nature conservation.